KEMAMPUAN PASSING BAWAH PERMAINAN VOLI PESERTA DIDIK KELAS VII B SMP NEGERI 19 KOTA JAMBI - Surya Hadi Prabowo; Atri Widowati; Bangkit Yudho Prabowo (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This research aims to determine the forearm pass skill level in volleyball among class VII B students of SMP Negeri 19 Kota Jambi. This study is a quantitative descriptive research using a survey method. The population in this study consisted of 13 students from class VII B of SMP Negeri 19 Kota Jambi. The sampling technique used was purposive sampling. The instrument used was the Brumbach forearm pass wall volley test to measure the forearm pass ability. The data analysis technique used was descriptive analysis with percentages. The results showed that the forearm pass ability of class VII B students at SMP Negeri 19 Kota Jambi was distributed into categories of excellent for 1 student (8%), good for 2 students (15%), average for 3 students (23%), below average for 6 students (46%), and poor for 1 student (8%). Overall, the forearm pass ability of class VII B students at SMP Negeri 19 Kota Jambi fell into the below average category with a mean score of 11.5. This is caused by a lack of mastery of proper forearm pass techniques, the absence of volleyball extracurricular activities at school, and minimal practice outside of school hours.